The Determinants of Skills of Canadian Immigrants - Hou, Yan Betty (University of Ottawa (Canada), 2011)
In this thesis, I present two empirical analyses to help understand the following question: Why do Canadian immigrants, despite their higher levels of education, have lower level of skill proficiencies than the native-born population in Canada? The first empirical analysis uses country-level macroeconomic data, while the second is conducted with individual level microeconomic data taken from International Adult Literacy Skill Survey (IALSS). In addition, the macro level and micro level results are compared at the end of the thesis. In the first part (Chapter 2), I summarize and synthesize the findings of previous research that addresses or helps in understanding the main questions analyzed in this thesis. I discuss the various approaches used to measure human capital and suggest that the literacy proficiency scores provided by IALSS are a more appropriate indicator than the commonly used educational data. I also discuss the various factors that play a role in the formation and development of immigrants' human capital, such as the income-per-capita in the country of origin, language proficiency, and education. The various data used in this thesis are discussed in Chapter 3. I have refined the coding of the country of origin in the original Master file of IALSS, extending the number of cross-sectional units from 28 countries to 50 countries/country-groups for the macro analysis. This is one contribution of my work, since the increase in the number of observations improves the robustness of the empirical analysis. The empirical analysis that used country-level macro data is carried out and presented in Chapter 4. All the results strongly suggest that the economic development level of the country of origin, proxied by the income per capita, is a key determinant of the immigrants' skill proficiency. The language barrier also plays an important role in explaining why immigrants have more years of schooling but lower skill proficiencies in Canada than the Canadian-born people. I also estimate regressions using employment earnings. The results concur with the analysis of Hanushek and Woessmann (2008), who show that education which did not contribute to cognitive skills will not affect the economic outcomes of immigrants. In Chapter 5, I turn to individual-level micro data to examine the factors linked with immigrants' skill proficiency. The micro level evidence also suggests that a country's economic development level that existed during an individual's schooling age plays an essential role for his/her future skill proficiency. The similar marginal effect for Canadian education and foreign education when income-per-capita of country of origin is under controlled suggests that income-per-capita of country of origin is a good proxy of quality of education. A comparison between individual and aggregated level regressions is discussed as well. Both micro-level and macro-level analyses provide consistent findings that income-per-capita of country of origin, years of schooling, and language proficiency in English/French have significant influences on immigrants' skill development. This type of comparison has not been conducted in previous studies in investigating the formation and development of immigrants' cognitive skills, and is considered as another contribution of this thesis.
Keywords: Economics, General.